Judicial System of Pakistan and Urdu Novel of 21st century, an Analytical Study: In the context of “Haider Goth Ka Bakshan” - Dr. Mushtaq Ahmad Imtiaz; Asima (Zaban-o-Adab, 2024)
Pakistan is facing many problems; the problems in the justice system are the most important. In our country, judges are not recruited on the basis of merit. Lawyers’ organizations, which are formed to protect the rights of lawyers, play an important role in the appointment of judges. Each organization tries to appoint judges from its own group, which affects impartiality. In our justice system, perjury, poor investigation, political influence and pressure from lawyers’ organizations are the problems that are affecting the efficiency of the justice system. Although this important issue has been written in novels like “Aik aur Darya”, “Jangloos”, “Nadar Lug” and “Judge Sahib”, but A novel that presents a complete picture of Nizam-e-Adl is "Haider Goth Ka Bakshan". The novelist Hafeez Khan has been a judge himself also and has seen this system from a very deep perspective. He has given a good picture of all the weaknesses, shortcomings and mistakes of the justice system. This novel is an important novel of the 21st century in terms of melody and panache.